Impact Of Covid-19 Pandemic At Tanjung Jabung Timur: Vegetable Traders Will Tell Us - daud daud (Jurnal Al Mujaddid Humaniora, 2021)
The pandemic period greatly affects various sides, one of which is in trade. Buying and selling activities in the market involve crowding which can facilitate the spread of the COVID. The activity that involves crowding that causes trade to decline. People tend to experience a decline in trading activities in the market. The study conducted a literature study to find the best strategy to increase selling using descriptive analysis. The results obtained that in the activity of trade and its influence on the spread of the virus obtained a new breakthrough. The breakthrough is by seeking to limit gathering activities through the vegetable trade through the WhatsApps distribution media.